THE EFFECT OF CAPITAL STRUCTURE AND LIQUIDITY ON PROFITABILITY OF PHARMACEUTICAL COMPANIES IN 2020-2024 - Dewi Astuti,; Ananta Amellia Haerunnisa, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The COVID-19 pandemic has brought major changes in the pharmaceutical industry, increasing demand for health products while challenging the financial stability of companies. In the midst of economic recovery, the efficiency of managing capital structure and liquidity is very important to maintain the profitability of pharmaceutical companies. This study aims to analyze the influence of capital structure and liquidity on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The method used is quantitative statistics where the approach is with the panel data regression analysis technique. Capital structure variables are measured using Debt to Equity Ratio (DER), liquidity with Current Ratio (CR), and profitability with Return on Assets (ROA). The sample used consisted of 7 companies selected based on specific criteria. The results show that partially, capital structure has a significant effect on profitability, while liquidity has no significant influence. However, simultaneously, these two variables have a significant influence on profitability with a contribution of 74.5%. These findings emphasize the importance of proper capital structure planning in an effort to improve the financial performance of pharmaceutical companies in the post-pandemic era.